(untitled) (Indian Journal of Child Health, 2017)
Background: Knowledge, attitude, and practices regarding the vaccines administered under the National Immunization Programme have been studied in different settings; however, studies regarding optional or newer vaccines in India are scarce. Objectives: To assess the parental knowledge about routine vaccination with special focus on newer vaccines and to identify the reasons for delay/non-administration of newer vaccines. Materials and Methods: This study is a cross-sectional study conducted in pediatric immunization clinic of MIMER Medical College, Talegaon (D) from May to September 2016. About 300 parents wereinterviewed with a semi open questionnaire. Results: Over all awareness and knowledge about the newer vaccines was very poor, i.e., only 32.5% of the total respondents. The majority (57.8%) of respondents was totally unaware about the optional vaccines and reasons for not administering the vaccines, despite being aware, were cost factor and travel constraints to the hospital which was present in 5% of the total respondents. Conclusion: Lack of knowledge among parents/caregivers about the optional vaccines and those who had knowledge regarding the vaccines, cost and distance to centers where they are available were the major constraints in immunization.